A colaboração crítica na compreensão e transformação do ensino-aprendizagem de inglês: atividade de formação de professor - Oliveira, Ana Paula de Francisco (2011)
This dissertation aims to critically understand the production of shared meanings among the participants of this research this researcher and an English teacher. Specifically, it aims to understand whether and how the relationship between researcher and teacher was constructed as a collaborative-critical process of production of shared knowledge, enabling changes in participants theoretical-practical understandings and in their actions. It was conducted with English learners in the 1st year of high school in a state school in the district of Pinheiros in the city of São Paulo. It is supported by contributions from Vygotsky (1930, 1934), Leontiev (1977) and Engeström (2001) in relation to Socio-Historical-Cultural Activity Theory (TASHC). Teacher training is seen as a socio-historical-cultural activity in which teacher and researcher are active participants in the production of shared meanings. The interaction pattern which was developed among participants is depicted as collaborativecritical, since it is a process in which argumentation and negotiation organize the production of new meanings. The adopted methodology is the Collaborative Critical Research (PCCol), which, as discussed by Magalhães and other members of LACE since 1990, works with critical and reflective training of the participants, proposing an investigation that does not separate theory from practice and promotes a transformation in practices. In order to analyze interaction between the participants, the researcher uses some categories of analysis based on Orsolini (2005), Pontecorvo (2005), Kerbrat-Orecchioni (1996) and Brookfield & Preskill (2005). The results show that the participants initial meanings about teaching-learning of English were reinterpreted, enabling them both not only to learn and to develop, but also to make changes in current practices in the classroom